Yucca Mountain pro and con [nuclear waste storage]. - Garrick, B.J.
It's just a lonely ridge of volcanic rock in Nevada, but it's generating more controversy than an indicted CEO. It's where the US Department of Energy wants to build a permanent underground repository for high-level nuclear waste. This paper discusses the arguments for and against Yucca Mountain.
Keywords: Nevada; US Department of Energy; Yucca Mountain; High-level nuclear waste; Nuclear waste storage; Permanent underground repository; Volcanic rock